The occurrence, types, reasons, and mitigation strategies of defensive medicine among physicians: a scoping review - Edris Kakemam; Morteza Arab-Zozani; Pouran Raeissi; Ahmed Hassan Albelbeisi (BMC, 2022)
Abstract Background Defensive Medicine (DM) concept refers to all medical care provided by physicians without increasing the benefits to the patient, the primary purpose of which is to prevent the risk of litigation. Although several studies have been published investigating the occurrence of DM around the world, no review conducted on DM among physicians. Therefore, this study aims to summarize and map the available evidence on occurrence, types of behaviors, and reasons for practicing of DM among physicians and possible solutions and strategies to reduce DM in the literature. Methods This is a scoping review in which we searched Web of Science, Scopus, and PubMed in December 2021. Our target was original studies of any type that included data on DM among physicians between 2000 and 2021. We followed the JBI guideline for conducting a scoping review and for increasing the rigor of the study. First, the percentage was used to summarize the occurrence of DM, and then, findings related to types of behaviors and reasons for practicing DM and mitigation strategies were analyzed inductively in NVivo 10 in three stages. Results Twenty-seven studies were included in the review. The overall occurrence of DM practice ranged from 6.7 to 99.8%. Two types of DM behaviors including assurance and avoidance behaviors have been identified. The common reasons for practicing DM were categorized into four themes, patient-related reasons, physician-related reasons, organization-related reasons, and society-related reasons. The main strategies to prevent or reduce DM are structured training and education, restoring physician-patient relationships, reform of the health system, and reform of the liability system. Conclusions The vast majority of research studies were conducted in high-income countries, and studies are needed to measure this phenomenon and its consequences in depth in low- and middle-income countries. Various solutions and strategies are needed to reduce defensive behaviors such as structured training and education, restoring physician-patient relationships, reforming the health system, and reforming the liability system. Keywords Defensive medicine, Defensive practice, Medical malpractice, Physicians, Scoping review